MENGINTEGRASIKAN PERMAINAN TRADISIONAL BALI (DOLANAN) PADA PENDIDIKAN ANAK SD SEBAGAI MEDIA PENDIDIKAN KARAKTER ANAK - MADE ADI NUGRAHA TRISTANINGRAT (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This study aims: 1) to Integrating Dolanan in the local content of Primary Education is the internalization of the value of character education into learning so that the result is an awareness of the importance of values, and 2) to forming a positive character for children and habituation of personality values into the behavior of everyday learners through learning process both in and out of the classroom. Culture can not be separated from society. Culture has become a major feature of a group of people and has been ingrained. Culture includes ideas in the human mind that are ethical and aesthetic. So in reality the culture is abstract. But its application can be observed from the behavior, language and art owned by a community. The culture will remain as long as the members of the community live and continue their noble culture. Along with the development of the times, technological progress also influence the cultural pattern of a society. Instead of bringing a positive impact to the culture, it is more affect the community to other cultures that in fact contradict the original culture of Indonesia. Take a look at the current trends, the minimal shirts that women wear, the lads who speak loudly to their parents, the cigarette smoking boy, and the